Standardised job submission and control in cluster and grid environments. (18th December 2008) - Troger, Peter; Rajic, Hrabri; Haas, Andreas; Domagalski, Piotr
Cluster and Grid environments mostly require the use of product-specific Application Programming Interface (APIs) to submit, control and monitor computational jobs. The Open Grid Forum standardisation body therefore has developed several specifications to fill the gap and enable developers to code to few standardised APIs. This paper discusses the details of one of these specifications, the Distributed Resource Management Application API. We compare the basic concepts of the finalised API to other specifications from the same area and explain issues and findings uncovered during the standardisation process.